Metoda porównawcza w prawoznawstwie i nauce historii prawa – próba rozwiązania wybranych problemów metodologicznych - Olejnik, Oskar (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The purpose of the article is to attempt to respond to selected methodological problems relevant to the comparative law, the most important of which is identified as linguistic barriers that hinder the correct comparison of legal institutions. Citing examples of translating the verb valoir present in Articles 1589 and 2279 of the Napoleonic Code into Polish and English, it was pointed out, following the example of the Louisiana Digest of 1808, that a descriptive approach is operative.
Keywords: legal methodology; mixed jurisdictions; Digest of 1808; Napoleonic Code; comparative law